Intelligent manufacturing planning - Gu, Peihua (Intelligent manufacturing series, 1995)
The integration of manufacturing planning functions, using artificial intelligence techniques, is essential for the effective and efficient operation of advanced manufacturing systems. This book provides an introduction to the integration of intelligent manufacturing systems for both present and next generation manufacturing. Because of its central importance, the book emphasizes the integration of the process planning functions.